A million junes ebook - Henry, Emily (2017)
"A beautiful, lyrical, and achingly brilliant story about love, grief, and family. Henry's writing will leave you breathless." —BuzzFeed Romeo and Juliet  meets  One Hundred Years of Solitude  in Emily Henry's brilliant follow-up to  The Love That Split the World , about the daughter and son of two long-feuding families who fall in love while trying to uncover the truth about the strange magic and harrowing curse that has plagued their bloodlines for generations.    In their hometown of Five Fingers, Michigan, the O'Donnells and the Angerts have mythic legacies. But for all the tall tales they weave, both founding families are tight-lipped about what caused the century-old rift between them, except to say it began with a cherry tree.   Eighteen-year-old Jack “June” O’Donnell doesn't need a better reason than that. She's an O'Donnell to her core, just like her late father was, and O'Donnells stay away from Angerts. Period.   But when Saul Angert, the son of June's father's mortal enemy, returns to town after three mysterious years away, June can't seem to avoid him. Soon the unthinkable happens: She finds she doesn't exactly hate the gruff, sarcastic boy she was born to loathe.    Saul’s arrival sparks a chain reaction, and as the magic, ghosts, and coywolves of Five Fingers conspire to reveal the truth about the dark moment that started the feud, June must question everything she knows about her family and the father she adored. And she must decide whether it's finally time for her—and all of the O'Donnells before her—to let go.